Building Indonesian National Defense in An Increasingly Complex Geostrategic Environment Through Education - Azzaziah, Raysa Nur; Kusumaryono, M.Si, Dr. Drs. R. Suyato (Journal Of Education, 2025)
Indonesia menghadapi tantangan ketahanan nasional yang semakin besar di tengah perubahan geostrategis di Asia Tenggara. Situasi ini menuntut upaya strategis untuk memperkuat ketahanan nasional, salah satunya melalui peran pendidikan. Artikel ini bertujuan untuk menganalisis bagaimana pendidikan dapat menjadi instrumen dalam memperkuat ketahanan nasional di tengah persaingan geopolitik yang kian intensif. Metode yang digunakan meliputi analisis literatur dan tinjauan data dari berbagai berita dan penelitian yang relevan. Temuan utama menunjukkan bahwa pendidikan memainkan peran penting dalam membangun kesadaran geopolitik, meningkatkan daya saing sumber daya manusia, dan memperkuat karakter bangsa. Dengan pendekatan pendidikan yang adaptif dan komprehensif, Indonesia dapat lebih siap menghadapi berbagai ancaman geostrategis. Kesimpulannya, pendidikan merupakan landasan vital untuk memperkuat ketahanan nasional di tengah dinamika Asia Tenggara yang semakin kompleks     Indonesia faces increasing challenges to its national resilience amidst shifting geostrategic dynamics in Southeast Asia. This situation requires strategic efforts to strengthen national resilience, with education playing a critical role. This article aims to analyze how education can serve as an instrument to enhance national resilience in the face of escalating geopolitical competition. The method used includes literature analysis and a review of data from various relevant news sources and studies. Key findings indicate that education plays an essential role in building geopolitical awareness, enhancing human resource competitiveness, and strengthening national character. Through an adaptive and comprehensive educational approach, Indonesia can better prepare for various geostrategic threats. In conclusion, education serves as a vital foundation for strengthening national resilience amid the increasingly complex dynamics in Southeast Asia.